PENGARUH HARGA DAN PROMOSI TERHADAP MINAT KONSUMEN (STUDI PADA PT. SAMUDRANESIA TOUR AND TRAVEL PEKANBARU) - Hendra Saputra; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine how the effect of incentives (material incentives and incentives non material) and work environment (physical work environment and work environment non fiisk) on employee job satisfaction (satisfaction with work, satisfaction with the system of rewards and job satisfaction of working conditions) 1912 mortgage Pekanbaru.The population in this study is karyaan in 1912 KPR Pekanbaru with sampling as many as 50 were drawn by using a questionnaire method. measurement techniques using Likert scale and the types and sources of data in the form of primary and secondary data while the data collection techniques with a questionnaire and interviews as research instruments. As well as using multiple linear regression data analysis, determination, t test and f test with SPSS.From the research data that includes test validity, The reliability, and multiple linear regression, the results showed no significant relationship between supervision terhaap employee performance with the calculated t of t test results are known (4.662)> t table (2,012) and Sig. (0,000) <0.05 can be concluded that the incentives variable significant effect on employee job satisfaction in 1912 KPR Pekanbaru and of the t test results are known t arithmetic (5.476)> t table (2,012) and Sig. (0.003) <0, 05 it can be concluded that the work environment variables significantly influence employee satisfaction in 1912 KPR Pekanbaru.And there is significant influence between Incentives and Work Environment on Job Satisfaction of employees with the calculated Unknown R squre is the coefficient of determination. And obtained a value of R squre 0.644. What this means is that the contribution of variable influence on the performance of supervision and loyalty of employees amounted to 64.6%. While the remaining 35.4% is influenced by other variables that are not included in the regression analysis.Keywords: Incentives, Work Environment and Employee Satis